Oxide solid electrolyte material and preparation method and application thereof
Through the preparation method of LBZrO solid electrolyte, the problems of high energy consumption and low purity in the preparation of oxide solid electrolytes are solved, and oxide solid electrolyte materials with high ionic conductivity and high compaction density are achieved, which are suitable for the field of new energy lithium batteries.
Patent Information
- Application Number
- CN202510102723.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing preparation technology of solid oxide electrolytes has problems such as high energy consumption, poor product purity control, low production efficiency, low ionic conductivity and low compaction density. It is urgent to develop a new oxide solid electrolyte material with high ionic conductivity, high compaction density, high purity, low cost and easy to prepare.
Using the preparation method of LBZrO solid electrolyte, the sintering temperature and atmosphere conditions are optimized to improve ion conduction and compaction density by mixing BLiO2, Li2O and B4Li2O7, and then mixing with zirconium source, lithium source and dopant.
It achieves the improvement of ionic conductivity and compaction density, reduces reaction temperature and energy consumption, improves the purity and production efficiency of the product, and has high-performance oxide solid electrolyte materials.
Smart Images

Figure CN119852507A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolyte material preparation, and in particular to an oxide solid electrolyte material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles, the demand for power batteries continues to increase. However, the core factors that affect or restrict the development of power batteries are resources such as nickel, cobalt, and lithium. Among them, lithium resources have a crucial impact on the cost of batteries and vehicles.
[0003] With the vigorous development of new energy technologies, various battery technologies with light weight, long battery life and high energy density have gradually improved. However, the safety and energy density of liquid lithium-ion batteries are inferior to those of solid or semi-solid batteries. The core key technology in semi-solid and solid batteries lies in the research and development and application of solid electrolytes. The current types of solid electrolytes are polymer solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, and nitride solid electrolytes, and each solid electrolyte has its own advantages and disadvantages.
[0004] Oxide electrolytes are compounds containing lithium, oxygen and other components (phosphorus / titanium / aluminum / lanthanum / germanium / zinc / zirconium, etc.), which are mainly divided into two categories: crystalline and amorphous. In the research technology, the amorphous state is mainly LiPON type, and the crystalline state includes garnet type, perovskite type, antiperovskite type, and fast ion type. Oxide solid electrolytes have the advantages of high safety, high thermal stability, wide electrochemical window, low cost, abundant resources, high mechanical strength, and relatively mature preparation process; however, traditional preparation technologies such as high-temperature solid-phase synthesis have inherent defects such as high energy consumption, poor product purity control, low production efficiency, low ionic conductivity, and low compaction density. An innovative preparation solution is urgently needed.
[0005] With the continuous progress of materials science and the research and synthesis of new materials with existing research technology, different types of oxides are constantly discovered and applied. Therefore, there is an urgent need to research and develop a new type of oxide solid electrolyte material with high ionic conductivity, high compaction density, high purity, low cost, high efficiency and easy preparation. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing an oxide solid electrolyte material. The method develops a LBZrO solid electrolyte. Compared with the traditional synthesis method of the same type of oxide solid electrolyte, the ion conductivity, purity and compaction density are improved while reducing the reaction temperature and improving the production efficiency, thereby achieving energy conservation and emission reduction and promoting green production.
[0007] A second object of the present invention is to provide an oxide solid electrolyte material prepared by the above preparation method.
[0008] The third object of the present invention is to provide an application of the above oxide solid electrolyte material in battery preparation.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a method for preparing an oxide solid electrolyte material, comprising the following steps:
[0011] (1) ball-milling BLiO2, Li2O and B4Li2O7 to obtain mixed lithium borate, and then pre-sintering to obtain pure lithium borate;
[0012] (2) dry-mixing and ball-milling the lithium borate obtained in step (1) with a zirconium source, a lithium source, and a dopant to obtain a mixture containing lithium zirconium borate; or,
[0013] The lithium borate obtained in step (1) is wet mixed with a slurry containing a zirconium source, a lithium source and a dopant, and then subjected to filter pressing and drying to obtain a mixture containing lithium zirconium borate;
[0014] wherein the dopant comprises a combination of TiO2, AlPO4, Al(OH)3 and Al2O3;
[0015] (3) tableting the mixture containing lithium zirconium borate obtained in step (2), sintering it once in an inert atmosphere, crushing it, and sieving it to obtain doped and modified lithium zirconium borate;
[0016] (4) mixing the doped modified lithium zirconium borate obtained in step (3) with the coating agent and ball milling, pressing the tablets, performing secondary sintering under an inert atmosphere, and crushing and sieving to obtain an oxide solid electrolyte material;
[0017] The coating agent includes a combination of a Ti / P compound, Al(OH)3, and a Li compound, wherein the Ti / P compound is TiP2O7 or Ti3(PO4)4, and the Li compound is C2H3O2Li or LiOH.
[0018] The following is a detailed description:
[0019] Step (1):
[0020] In some embodiments, the purity of BLiO2, Li2O, and B4Li2O7 in step (1) is ≥99.9%, and the D50 particle size thereof is 1.0 μm to 15.0 μm, preferably 2.0 μm to 12.0 μm, and more preferably 2.0 μm to 8.0 μm;
[0021] In some embodiments, the mass ratio of BLiO2, Li2O and B4Li2O7 in step (1) is 0.6-1:0.6-1:0.5-1, preferably 0.8-1:0.8-1:0.6-1, and more preferably 1:1:1;
[0022] The mixed ball milling equipment is a high-energy ball mill, a ball mill, a pot mill, etc.; the mixed ball milling medium is one of zirconia balls, agate balls, stainless steel grinding balls, and hard alloy grinding balls, preferably zirconia balls or agate balls.
[0023] In some embodiments, the rotation speed of the mixing ball mill in step (1) is 100 to 1500 rpm, preferably 200 to 1400 rpm, and more preferably 300 to 1280 rpm; the mixing ball milling time is 0.5 to 8.0 h, preferably 1 to 6.0 h, and more preferably 2.0 to 5.0 h; the ball-to-material ratio of the mixing ball mill is 2 to 20:1, preferably 3 to 18:1, and more preferably 3 to 12:1;
[0024] In some embodiments, the initial lithium borate particle size after mixing and ball milling in step (1) is 0.8-1.2 μm;
[0025] The pre-sintering equipment is one of a microwave synthesizer, a microwave reactor, a microwave catalytic synthesizer, a vacuum box atmosphere furnace, a vacuum tube furnace, and a rotary furnace; preferably, a microwave catalytic synthesizer and a vacuum box atmosphere furnace.
[0026] In some embodiments, the pre-sintering temperature in step (1) is 100 to 800° C., preferably 200 to 740° C., more preferably 300 to 680° C.; the pre-sintering constant temperature time is 1 to 6.0 h, preferably 1.5 to 5.0 h, more preferably 2.0 to 4.0 h;
[0027] In some embodiments, the pre-sintering atmosphere in step (1) is one of argon and nitrogen;
[0028] Step (2):
[0029] In some embodiments, the zirconium source in step (2) is selected from Zr(CO3)2, Zr(OH)4, ZrO2, Zr 0.92 O2Y 0.08 、Zr 0.97 O2Y 0.03 , Zr(CH3COO)4, ZrB2, ZrF4, ZrSiO4, Li2ZrO3, Zr(HPO4)2, ZrCl4, Zr(CH3COO)4·4H2O, Zr(C6H5O7)2, Zr(NO3)4, ZrS2; preferably, the zirconium source is Zr(CO3)2, Zr(OH)4, ZrO2, Zr 0.92 O2Y0.08 、Zr 0.97 O2Y 0.03 One or more of the following;
[0030] In some embodiments, the lithium source in step (2) is one or more selected from LiOH, LiOH·H2O, Li2CO3, LiNO3, Li3BO3, LiBO2, Li2O, LiI, LiCl or C2H3O2Li; preferably, the lithium source is one or more selected from Li2O, Li2CO3, LiOH·H2O;
[0031] In some embodiments, the mass of the dopant in step (2) accounts for 0.01% to 6% of the total mass of the lithium source, lithium borate and zirconium source, preferably 0.04% to 4%, more preferably 0.06% to 3%, wherein the mass ratio of the lithium source, lithium borate, zirconium source and dopant is 1 to 10: 1 to 3: 1 to 3, preferably 2 to 8: 1 to 2: 1 to 2, more preferably 2 to 6: 1: 1;
[0032] The mass ratio here refers to the mass ratio of dry powder. If the wet method is used, it refers to the mass of the corresponding dry powder in the slurry. The total solid content of lithium source, zirconium source and dopant in the wet method slurry is 20-50%, preferably 25-40%, more preferably 28-35%, and the slurry solvent is pure water.
[0033] Preferably, the zirconium source is ZrO2 or Zr 0.92 O2Y 0.08 or Zr 0.97 O2Y 0.03 Purity ≥ 99.9%, D50 particle size 0.02 μm to 2.0 μm, preferably 0.02 μm to 1.5 μm, more preferably 0.04 μm to 1.0 μm;
[0034] Preferably, the purity of the zirconium source Zr(CO3)2 or Zr(OH)4 is ≥99.5%, and its D50 particle size is 0.04 μm to 3.0 μm, preferably 0.04 μm to 2.0 μm, and more preferably 0.4 μm to 1.5 μm;
[0035] Preferably, the purity of the lithium source Li2O is ≥99.9%, and its D50 particle size is 1.0 μm to 10.0 μm, preferably 2.0 μm to 8.0 μm, and more preferably 2.0 μm to 5.0 μm;
[0036] Preferably, the purity of the lithium source Li2CO3 is ≥99.5%, and its D50 particle size is 1.0 μm to 10.0 μm, preferably 2.0 μm to 8.0 μm, and more preferably 2.0 μm to 5.0 μm;
[0037] Preferably, the purity of the lithium source LiOH·H2O is ≥99.0%, and its D50 particle size is 1.0 μm to 10.0 μm, preferably 2.0 μm to 8.0 μm, and more preferably 2.0 μm to 5.0 μm;
[0038] In some embodiments, the mass ratio of the total mass of the lithium source, lithium borate and zirconium source to TiO2 in step (2) is 1.0:0.0001-0.02, preferably 1:0.0004-0.015, and more preferably 1:0.0006-0.01;
[0039] The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to AlPO4 is 1.0:0.0001-0.02, preferably 1:0.0004-0.015, and more preferably 1:0.0006-0.01;
[0040] The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to Al(OH)3 is 1.0:0.0001-0.020, preferably 1:0.0004-0.020, and more preferably 1:0.0006-0.018;
[0041] The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to Al2O3 is 1.0:0.0001-0.06, preferably 1:0.0004-0.04, and more preferably 1:0.0006-0.03.
[0042] Preferably, the purity of TiO2 is ≥99.9%, and its D50 particle size is 0.04 μm to 5.0 μm, preferably 0.1 μm to 4.0 μm, and more preferably 0.4 μm to 3.0 μm;
[0043] Preferably, the purity of AlPO4 is ≥99.9%, and its D50 particle size is 0.05 μm to 4.0 μm, preferably 0.1 μm to 3.0 μm, and more preferably 0.3 μm to 3.0 μm;
[0044] Preferably, the purity of Al(OH)3 is ≥99.9%, and its D50 particle size is 0.04 μm to 6.0 μm, preferably 0.1 μm to 5.0 μm, and more preferably 0.4 μm to 3.0 μm.
[0045] Preferably, the purity of Al2O3 is ≥99.9%, and its D50 particle size is 0.04 μm to 6.0 μm, preferably 0.1 μm to 5.0 μm, and more preferably 0.4 μm to 3.0 μm.
[0046] In some embodiments, the rotation speed of the dry and wet mixed ball milling in step (2) is 200 to 2500 rpm, preferably 300 to 2200 rpm, and more preferably 1000 to 2200 rpm;
[0047] The time of dry and wet mixed ball milling is 1.0 to 10.0 h, preferably 2.0 to 8.0 h, more preferably 3.0 to 6.0 h;
[0048] The ball-to-material ratio of dry and wet mixed ball milling is 3 to 20:1, preferably 4 to 18:1, and more preferably 5 to 12:1;
[0049] In some embodiments, the particle size of the mixture containing lithium zirconium borate after mixed ball milling in step (2) is 0.7-1.0 μm.
[0050] Step (3):
[0051] The mixture containing lithium zirconium borate is loaded into a corundum sagger for tableting and then transferred to a sintering device for high-temperature primary sintering under a slightly positive or negative pressure inert atmosphere (argon or nitrogen), and then subjected to air flow crushing, screening and demagnetization to obtain a doped and modified lithium zirconium borate product.
[0052] In some embodiments, the tableting pressure in step (3) is 18 to 36 MPa, preferably 20 to 34 MPa, and more preferably 24 to 32 MPa; the tableting time is 1 to 20 s, preferably 2 to 15 s, and more preferably 3 to 10 s;
[0053] The sintering equipment is a vacuum box atmosphere furnace, a vacuum tube furnace, or an atmosphere roller kiln, preferably a vacuum box atmosphere furnace or an atmosphere roller kiln;
[0054] In some embodiments, the primary sintering temperature in step (3) is 200 to 2400° C., preferably 400 to 1800° C., more preferably 600 to 1500° C.; the primary sintering time is 2 to 32 hours, preferably 3 to 24 hours, more preferably 3 to 18 hours;
[0055] In some embodiments, the pressure of the primary sintering in step (3) is a slight positive pressure or a slight negative pressure, the slight positive pressure is 10 to 200 Pa, preferably 15 to 120 Pa, more preferably 20 to 100 Pa, the slight negative pressure is -15 to -180 Pa, preferably -18 to -120 Pa, more preferably -25 to -100 Pa.
[0056] In some embodiments, the particle size of the doped modified lithium zirconium borate obtained in step (3) is 300 nm-1.0 μm.
[0057] Step (4):
[0058] The doped modified lithium zirconium borate is dry-mixed with the coating agent and ball-milled, then loaded into a corundum sagger for tableting and transferred to a sintering device for high-temperature secondary sintering under a slightly positive or negative pressure inert atmosphere (argon or nitrogen), and then crushed, sieved and demagnetized to obtain the coated modified lithium zirconium borate product.
[0059] In some embodiments, the mass ratio of the doped modified lithium zirconium borate to the total amount of the coating agent in step (4) is 1:0.0001-0.040, preferably 1:0.0004-0.036, and more preferably 1:0.0006-0.032;
[0060] Preferably, the mass ratio of doped modified lithium zirconium borate to C2H3O2Li is 1:0.0001-0.020, preferably 1:0.0002-0.018, more preferably 1:0.0003-0.016;
[0061] The mass ratio of doped modified lithium zirconium borate to LiOH is 1:0.0001-0.020, preferably 1:0.0002-0.018, and more preferably 1:0.0003-0.016;
[0062] The mass ratio of doped modified lithium zirconium borate to TiP2O7 is 1:0.0001-0.020, preferably 1:0.0002-0.018, and more preferably 1:0.0003-0.016;
[0063] The mass ratio of doped modified lithium zirconium borate to Ti3(PO4)4 is 1:0.0001-0.010, preferably 1:0.0002-0.009, more preferably 1:0.0003-0.008;
[0064] The mass ratio of doped modified lithium zirconium borate to Al(OH)3 is 1:0.0001-0.010, preferably 1:0.0002-0.009, more preferably 1:0.0003-0.008;
[0065] Preferably, the purity of anhydrous C2H3O2Li is ≥99.0%, and its D 50 Particle size is 20nm-100nm;
[0066] Preferably, the purity of anhydrous LiOH is ≥99.5%, and its D50 particle size is 20nm-100nm;
[0067] Preferably, the purity of TiP2O7 is ≥99.0%, and its D50 particle size is 200nm-500nm;
[0068] Preferably, the purity of Ti3(PO4)4 is ≥99.0%, and its D50 particle size is 200nm-500nm;
[0069] Preferably, the purity of Al(OH)3 is ≥99.5%, and its D50 particle size is 200nm-500nm.
[0070] In some embodiments, the tableting pressure in step (4) is 10 to 20 MPa, preferably 12 to 18 MPa, and more preferably 14 to 16 MPa; the tableting time is 1 to 10 s, preferably 2 to 8 s, and more preferably 3 to 6 s;
[0071] The sintering equipment is a vacuum box atmosphere furnace, a vacuum tube furnace, or an atmosphere roller kiln, preferably a vacuum box atmosphere furnace or an atmosphere roller kiln;
[0072] In some embodiments, the secondary sintering temperature in step (4) is 100-1100° C., preferably 150-1000° C., more preferably 200-980° C.; the secondary sintering time is 1-10 h, preferably 1.5-8 h, more preferably 2-6 h;
[0073] In some embodiments, the pressure of the secondary sintering in step (4) is a slight positive pressure or a slight negative pressure, the slight positive pressure is 10 to 150 Pa, preferably 15 to 100 Pa, more preferably 20 to 80 Pa, the slight negative pressure is -15 to -150 Pa, preferably -18 to -100 Pa, more preferably -25 to -80 Pa.
[0074] In some embodiments, the particle size of the oxide solid electrolyte material obtained in step (4) is 50 nm to 900 nm.
[0075] In a second aspect, the present invention provides an oxide solid electrolyte material prepared by the above preparation method.
[0076] The prepared oxide solid electrolytic lithium zirconium borate (LZBO) has the general chemical formula: Li a Zr x B y M b O3, wherein 1.0≤a≤10.0, 1.0≤x≤3.0, 1.0≤y≤3.0, 0<b≤0.13, M is the total molar sum of Ti, Al, P doping and surface doping coating.
[0077] The lithium zirconium borate (LZBO) solid electrolyte prepared by the method is an inorganic material with multiple functional properties, and has the characteristics of high ionic conductivity, high compaction density, high purity, and easy processing of electronic-grade functional materials. It has significant application value in the fields of positive and negative electrode material modification, slurry and electrode modification, diaphragm coating, ceramics, glass, catalysts, etc. related to new energy lithium batteries.
[0078] In a third aspect, the present invention provides an application of an oxide solid electrolyte material in the preparation of a secondary battery.
[0079] Application in the technical field of all-solid-state batteries and semi-solid-state batteries; preferably, the secondary battery is a lithium-ion battery.
[0080] Technical effect:
[0081] The method of the present invention improves the ionic conductivity and compaction density of lithium zirconium borate (LZBO) by innovating the raw material combination, reduces the residual alkali content, effectively reduces the reaction temperature, and reduces energy consumption.
[0082] The method of the present invention significantly improves the purity of the product by introducing specific additives to improve the solid phase reaction;
[0083] The method of the present invention further improves the performance of lithium zirconium borate (LZBO) through secondary high-temperature modification;
[0084] The method of the present invention is simple to operate, and the obtained product has high purity and low impurity content, and has the performance characteristics and application advantages of solid electrolytes related to the new energy field.
[0085] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 This is a process flow chart of the preparation method of the oxide solid electrolyte material of the present invention;
[0087] Figure 2 The SEM images of the solid electrolyte materials prepared in Examples 1-3 of the present invention; DETAILED DESCRIPTION
[0088] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0089] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0090] In the following embodiments of the present invention, the selected lithium metaborate, lithium oxide, lithium boride, zirconium source, lithium source, dopant, and coating agent can be purchased from the market with the same required specifications, or can be prepared according to traditional synthesis methods.
[0091] Example 1
[0092] A method for preparing an oxide solid electrolyte material, such as Figure 1 As shown, the following steps are included:
[0093] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball mill at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 is in the range of 0.8-1.2 μm. Then transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0094] (2) Weigh Li2O (D50: 2.5 μm), Zr 0.97 O2Y 0.03 100 g, 50 g, 50 g, 1.28 g, 0.40 g, 0.44 g and 0.36 g of powders of lithium borate (D50: 2.0 μm), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm) and Al(OH)3 (D50: 1.0 μm) respectively, are put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball milled at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0095] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0096] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.264g, 0.432g, and 0.216g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic particles were screened to obtain the coated and modified lithium zirconium borate (LZBO) finished product. SEM pictures Figure 2 shown.
[0097] Example 2
[0098] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0099] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball mill at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 is in the range of 0.8-1.2 μm. Then transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0100] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08 100 g, 50 g, 50 g, 0.96 g, 0.36 g, 0.36 g, 0.24 g of powders of lithium borate (D50: 2.0 μm), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm), and Al(OH)3 (D50: 1.0 μm), respectively, were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 was in the range of 0.7-1.0 μm;
[0101] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0102] (4) Weigh 120g, 0.312g, 0.456g and 0.216g of the lithium zirconium borate matrix obtained by doping and modification in step (3), TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm) and C2H3O2Li (D50: 80nm), respectively, and put them into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball mill at 1800rpm for 4.0h, then put them into a corundum sagger and press them into tablets at 15MPa for 5s, then transfer them into a vacuum box atmosphere furnace and heat them to 460℃ at 5℃ / min and keep the temperature constant for 1.0h under dry air, then heat them to 800℃ at 5℃ / min and keep the temperature constant for 3.0h, then cool them down and put them into a jet mill to crush them into 50nm-900nm, and finally screen out the magnetic particles to obtain the finished product of lithium zirconium borate (LZBO) after coating and modification. SEM picture as shown Figure 2 shown.
[0103] Example 3
[0104] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0105] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0106] (2) Weigh LiOH·H2O (D50: 2.5 μm), Zr 0.97 O2Y 0.03 150 g, 50 g, 50 g, 1.95 g, 0.55 g, 0.60 g, and 0.70 g of powders of the lithium borate (D50: 2.0 μm), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm), and Al(OH)3 (D50: 1.0 μm) obtained in step (1) are put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball milled at 2000 rpm for 5.0 hours. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0107] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0108] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), C2H3O2Li (D50: 80nm) were weighed 120g, 0.264g, 0.432g, and 0.216g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball-milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the coated and modified lithium zirconium borate (LZBO) finished product was obtained after sieving out the magnetic particles. SEM picture as shown Figure 2 shown.
[0109] Example 4
[0110] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0111] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0112] (2) Weigh 100 g, 50 g, 50 g, 1.92 g, 0.40 g, 0.56 g, and 0.84 g of powders of Li2CO3 (D50: 2.5 μm), Zr(CO3)2 (D50: 2.0 μm), lithium borate (D50: 1.1 μm) obtained in step (1), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm), and Al(OH)3 (D50: 1.0 μm), respectively, and put them into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball mill them at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0113] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 300 nm-1.0 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0114] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.288g, 0.576g, and 0.264g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic particles were screened to obtain the coated and modified lithium zirconium borate (LZBO) finished product.
[0115] Example 5
[0116] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0117] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball mill at 1200 rpm for 4.0 h. Samples were taken and tested for laser particle size D50 = 1.1 μm. Then, they were transferred to a microwave catalytic synthesizer, argon was introduced, and the temperature was raised to 600 °C at 5 °C / min and kept constant for 2.0 h.
[0118] (2) Weigh 100 g, 50 g, 50 g, 1.92 g, 0.40 g, 0.56 g, and 0.84 g of powders of Li2CO3 (D50: 2.5 μm), Zr(OH)4 (D50: 2.0 μm), lithium borate (D50: 1.1 μm) obtained in step (1), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm), and Al(OH)3 (D50: 1.0 μm), respectively, put them into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball mill them at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0119] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0120] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.288g, 0.576g, and 0.264g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball-milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred into a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic impurities were screened out to obtain the finished lithium zirconium borate (LZBO) product after coating and modification.
[0121] Example 6
[0122] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0123] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0124] (2) Weigh 100 g, 50 g, 50 g, 1.92 g, 0.40 g, 0.56 g, and 0.84 g of powders of Li2CO3 (D50: 2.5 μm), ZrO2 (D50: 2.0 μm), lithium borate (D50: 1.1 μm) obtained in step (1), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm), and Al(OH)3 (D50: 1.0 μm), respectively, put them into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball mill them at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0125] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0126] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.288g, 0.576g, and 0.264g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball-milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred into a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic impurities were screened out to obtain the finished lithium zirconium borate (LZBO) product after coating and modification.
[0127] Example 7
[0128] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0129] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0130] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08100 g, 50 g, 50 g, 0.96 g, 0.36 g, 0.40 g and 0.32 g of powders of lithium borate (D50: 2.0 μm), lithium borate (D50: 1.1 μm), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm) and Al(OH)3 (D50: 1.0 μm) respectively, were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 was in the range of 0.7-1.0 μm;
[0131] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0132] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and Ti3(PO4)4 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.216g, 0.432g, and 0.216g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic impurities were screened out to obtain the finished lithium zirconium borate (LZBO) product after coating and modification.
[0133] Example 8
[0134] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0135] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0136] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08 100 g, 50 g, 50 g, 0.96 g, 0.36 g, 0.40 g and 0.32 g of powders of lithium borate (D50: 2.0 μm), lithium borate (D50: 1.1 μm), TiO2 (D50: 1.0 μm), AlPO4 (D50: 1.0 μm), Al2O3 (D50: 1.0 μm) and Al(OH)3 (D50: 1.0 μm) respectively, are put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball milled at 2000 rpm for 5.0 h. After ball milling, the particle size of D50 is in the range of 0.7-1.0 μm;
[0137] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0138] (4) The lithium zirconium borate (LZBO) matrix obtained by doping and modification in step (3) and Ti3(PO4)4 (D50: 300nm), Al(OH)3 (D50: 300nm), and LiOH (D50: 80nm) were weighed 120g, 0.240g, 0.492g, and 0.252g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball-milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic impurities were screened out to obtain the finished lithium zirconium borate (LZBO) product after coating and modification.
[0139] Example 9
[0140] A method for preparing an oxide solid electrolyte material comprises the following steps:
[0141] (1) First, weigh 50 g (D50: 2.5 μm) of BLiO2, Li2O, and B4Li2O7 powders, put them into a high-energy mixing ball mill at a ball-to-material ratio of 8:1, and then ball milled at 1200 rpm for 4.0 h. After ball milling, the particle size of D50 was in the range of 0.8-1.2 μm. Then, transfer them to a microwave catalytic synthesizer, introduce argon gas, and heat them to 600°C at 5°C / min and keep the temperature constant for 2.0 h;
[0142] (2) Weigh Li2CO3 (D50: 2.5 μm), lithium borate powder (D50: 1.1 μm) obtained in step (1) and Zr with a solid content of 30% 0.92 O2Y 0.08 100g, 50g, 166.67g, 3.2g, 1.2g, 1.2g, 0.80g of slurry of TiO2 (D50: 2.0μm), TiO2 (D50: 1.0μm), AlPO4 (D50: 1.0μm), Al2O3 (D50: 1.0μm), Al(OH)3 (D50: 1.0μm) and 350g of pure water are put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and wet-milled at 1800rpm for 4.0h. After ball milling, the D50 particle size range is 0.7-1.0μm; then the slurry obtained by ball milling is spray-dried, and the moisture content of the dried material is less than 1.5%;
[0143] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.0 μm, and finally the magnetic particles are screened to obtain a doped and modified lithium zirconium borate (LZBO) matrix;
[0144] (4) The lithium zirconium borate matrix obtained by doping and modification in step (3) and TiP2O7 (D50: 300nm), Al(OH)3 (D50: 300nm), and C2H3O2Li (D50: 80nm) were weighed 120g, 0.312g, 0.456g, and 0.216g, respectively, and put into a high-energy mixing ball mill according to a ball-to-material ratio of 10:1, and ball-milled at 1800rpm for 4.0h, then put into a corundum sagger and pressed into tablets at 15MPa for 5s, and then transferred to a vacuum box atmosphere furnace and heated to 460℃ at 5℃ / min and kept at a constant temperature for 1.0h under dry air, and then heated to 800℃ at 5℃ / min and kept at a constant temperature for 3.0h, and then cooled and put into a jet mill to crush into 50nm-900nm, and finally the magnetic particles were screened out to obtain the coated and modified lithium zirconium borate (LZBO) finished product.
[0145] Comparative Example 1
[0146] The difference from Example 2 is that only one high-temperature synthesis is used, and no doping and coating are performed, and the following steps are included:
[0147] (1) Same as Example 2;
[0148] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08 100 g, 50 g, and 50 g of the powder of lithium borate (D50: 2.0 μm) obtained in step (1) (D50: 1.1 μm) were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. The sample was taken and tested by a laser particle size analyzer to have a D50 of 1.2 μm.
[0149] (3) The material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred to a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, then cooled to 1000° C. at 5° C. / min for 6.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 50 nm-900 nm, and finally screened to remove the magnetism to obtain lithium zirconium borate (LZBO).
[0150] Comparative Example 2
[0151] The difference from Example 2 is that no relevant element doping modification is performed, and the method comprises the following steps:
[0152] (1) Same as Example 2;
[0153] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08 100 g, 50 g, and 50 g of the powder of lithium borate (D50: 2.0 μm) obtained in step (1) (D50: 1.1 μm) were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. The sample was taken and tested by a laser particle size analyzer to have a D50 of 1.2 μm.
[0154] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 1000° C. at 5° C. / min for 6.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally screened to remove the magnetic material to obtain a lithium zirconium borate (LZBO) matrix;
[0155] (4) Same as Example 2.
[0156] Comparative Example 3
[0157] The difference from Example 2 is that no coating and secondary sintering are performed, and the following steps are included:
[0158] (1) and (2) are the same as in Example 2;
[0159] (3) The material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred to a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, then cooled to 1000° C. at 5° C. / min for 6.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally screened to remove the magnetism to obtain lithium zirconium borate (LZBO).
[0160] Comparative Example 4
[0161] The difference from Example 2 is that lithium zirconium borate (LZBO) is synthesized by a one-step method without doping and coating, and includes the following steps:
[0162] Weigh Li2CO3 (D50: 2.5μm), Zr 0.92 O2Y 0.08 120g, 60g, 20g, 20g, and 20g of each of B4Li2O7 (D50: 2.5μm), BLiO2 (D50: 2.5um), Li2O (D50: 2.5μm), and B4Li2O7 (D50: 2.5μm) were put into a high-energy mixed ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000rpm for 12.0h; then the material obtained by the mixed ball milling was put into a corundum sagger and pressed into tablets at 28MPa for 8s, transferred into a vacuum box atmosphere furnace and heated to 1400℃ at 5℃ / min under dry air for 1.0h, then cooled to 1100℃ at 5℃ / min for 12.0h, then cooled to 280℃ at 5℃ / min for 1.0h, then cooled to 5℃ / min for 1.0h, then put into a jet mill after cooling and crushed to 50nm-900nm, and finally screened out the magnetism to obtain lithium zirconium borate (LZBO).
[0163] Comparative Example 5
[0164] The difference from Example 2 is that only one high-temperature synthesis is used, the sintering conditions remain unchanged, and no doping and coating are performed, and the following steps are included:
[0165] (1) Same as Example 2;
[0166] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08100 g, 50 g, and 50 g of the powder of lithium borate (D50: 2.0 μm) obtained in step (1) (D50: 1.1 μm) were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. The sample was taken and tested by a laser particle size analyzer to have a D50 of 1.2 μm.
[0167] (3) The material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred to a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 50 nm-900 nm, and finally screened to remove the magnetism to obtain lithium zirconium borate (LZBO).
[0168] Comparative Example 6
[0169] The difference from Example 2 is that the sintering conditions remain unchanged and no relevant element doping modification is performed, and the following steps are included:
[0170] (1) Same as Example 2;
[0171] (2) Weigh Li2CO3 (D50: 2.5 μm), Zr 0.92 O2Y 0.08 100 g, 50 g, and 50 g of the powder of lithium borate (D50: 2.0 μm) obtained in step (1) (D50: 1.1 μm) were put into a high-energy mixing ball mill at a ball-to-material ratio of 10:1, and ball-milled at 2000 rpm for 5.0 h. The sample was taken and tested by a laser particle size analyzer to have a D50 of 1.2 μm.
[0172] (3) the material obtained by the mixed ball milling in step (2) is placed in a corundum sagger and pressed into a tablet at 28 MPa for 8 seconds, and then transferred into a vacuum box atmosphere furnace and heated to 1200° C. at 5° C. / min under dry air for 1.0 h, and then cooled to 850° C. at 5° C. / min for 4.0 h, and then cooled to 280° C. at 5° C. / min for 1.0 h, and then cooled and put into a jet mill to crush into 500 nm-1.2 μm, and finally screened to remove the magnetic material to obtain a lithium zirconium borate (LZBO) matrix;
[0173] (4) Same as Example 2.
[0174] Experimental example
[0175] 1. Physical and chemical properties test
[0176] The oxide solid electrolytes prepared in the above examples and comparative examples were tested for physical and chemical indicators such as particle size, tap density, purity, moisture, residual alkali, and ionic conductivity. The results are shown in Table 1:
[0177] Table 1 Physical and chemical index test results of each embodiment and comparative example
[0178] Particle size D50(nm) <![CDATA[Tap density g / cm 3 > purity% Moisture ppm Residual alkali ppm Ionic conductivity S / cm Appearance Color Particle morphology Example 1 394 1.62 99.81 232 6652 <![CDATA[5.62×10 -4 ]]> White Single particle spherical and quasi-spherical Example 2 376 1.65 99.84 214 6430 <![CDATA[7.78×10 -4 ]]> White Single particle spherical and quasi-spherical Example 3 382 1.63 99.83 186 6346 <![CDATA[6.64×10 -4 ]]> White Single particle spherical and quasi-spherical Example 4 458 1.64 99.82 202 6620 <![CDATA[4.41×10 -4 ]]> White Single particle spherical and quasi-spherical Example 5 412 1.62 99.83 241 6458 <![CDATA[4.58×10 -4 ]]> White Single particle spherical and quasi-spherical Example 6 426 1.67 99.85 180 6786 <![CDATA[5.14×10 -4 ]]> White Single particle spherical and quasi-spherical Example 7 404 1.64 99.83 196 6543 <![CDATA[7.46×10 -4 ]]> White Single particle spherical and quasi-spherical Example 8 431 1.63 99.82 218 6428 <![CDATA[7.35×10 -4 ]]> White Single particle spherical and quasi-spherical Example 9 360 1.64 99.83 238 5160 <![CDATA[7.62×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 1 398 1.34 99.63 316 8184 <![CDATA[2.38×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 2 402 1.38 99.68 283 8041 <![CDATA[2.46×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 3 395 1.42 99.65 294 8235 <![CDATA[2.31×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 4 386 1.25 99.52 335 9246 <![CDATA[1.26×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 5 382 1.22 99.51 402 9682 <![CDATA[1.28×10 -4 ]]> White Single particle spherical and quasi-spherical Comparative Example 6 391 1.21 99.48 365 9431 <![CDATA[1.48×10 -4 ]]> White Single particle spherical and quasi-spherical
[0179] It can be seen from the test data in Table 1 that the ionic conductivity of LZBO oxide solid electrolyte powder after surface doping modification with a certain amount of Ti / Al / P doping and Ti / Al / P / Li synergistic coating is significantly improved. The addition amount of different modifying elements and different raw materials, holding temperature, cooling rate and other process parameters all play a role in the improvement of ionic conductivity and there are certain differences.
[0180] 2. Rate performance test
[0181] The rate performance of the oxide solid electrolytes prepared in the above examples and comparative examples was tested and evaluated according to the following method.
[0182] Make a solid-state battery with Ni650728 nickel cobalt manganese oxide as the positive electrode and metal lithium as the negative electrode, and evaluate the rate performance and cycle performance of the oxide solid electrolyte. The specific operation method is as follows:
[0183] 1) Ni650728 nickel cobalt manganese oxide, binder PVDF (polyvinylidene fluoride), CNT, conductive agent Super P, solid electrolyte (LZBO) were mixed in a mass ratio of 96.5:1.2:0.6:0.7:1.0, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added and stirred to prepare a positive electrode slurry (solid content 73%), which was coated on aluminum foil, dried at 105°C, and then cut into discs with a diameter of 10 mm as positive electrode sheets.
[0184] 2) The solid electrolyte LZBO (75%) and PEO (25%) were mixed and ground for 3 h, and then heated at 95 °C.
[0185] / 6.8Mpa hot pressing to obtain a solid electrolyte membrane with a thickness of about 85μm.
[0186] 3) Assemble a CR2032 button cell in the order of positive electrode sheet-solid electrolyte membrane-lithium foil and conduct battery rate and cycle tests.
[0187] The operating voltage range of the lithium secondary battery is set to 3.0V-4.40V, and it is charged to 4.40V at a constant current of 0.1C, and then the constant voltage is cut off at 0.01C; then the current is discharged to 3.0V at 0.1C, 0.2C, 0.5C, 1.0C, and 2.0C respectively, and the gram-specific capacity of the material at the discharge rate of 0.1C, 0.2C, 0.5C, 1.0C, and 2.0C is obtained respectively, and then 1C / 1C. The test results are shown in Table 2:
[0188] Table 2: Test results of various embodiments and comparative examples
[0189]
[0190] It can be seen from the test data in Table 2 that the rate and cycle performance of the LZBO oxide solid electrolyte powder modified by a certain amount of Ti / Al / P doping and Ti / Al / P / Li synergistic coating surface doping are significantly improved compared with the control example, and the process parameters all play a role in the improvement of ionic conductivity and there are certain differences.
[0191] It can be seen that the lithium zirconium borate (LZBO) prepared based on the preparation method and process system of the oxide solid electrolyte material can meet the relevant performance indicators of similar oxide solid electrolytes.
[0192] The technical solutions of the above embodiments are merely preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solutions of the present invention.
[0193] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may be modified, or some or all of the technical features therein may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing an oxide solid electrolyte material, characterized in that: The following steps are involved: (1) ball-milling BLiO2, Li2O and B4Li2O7 to obtain mixed lithium borate, and then pre-sintering to obtain pure lithium borate; (2) dry-mixing and ball-milling the lithium borate obtained in step (1) with a zirconium source, a lithium source, and a dopant to obtain a mixture containing lithium zirconium borate; or, The lithium borate obtained in step (1) is wet mixed with a slurry containing a zirconium source, a lithium source and a dopant, and then subjected to filter pressing and drying to obtain a mixture containing lithium zirconium borate; wherein the dopant comprises a combination of TiO2, AlPO4, Al(OH)3 and Al2O3; (3) tableting the mixture containing lithium zirconium borate obtained in step (2), sintering it once in an inert atmosphere, and crushing and sieving it to obtain doped and modified lithium zirconium borate; (4) mixing the doped modified lithium zirconium borate obtained in step (3) with the coating agent and ball milling, pressing the tablets, performing secondary sintering under an inert atmosphere, and crushing and sieving to obtain an oxide solid electrolyte material; The coating agent includes a combination of a Ti / P compound, Al(OH)3, and a Li compound, wherein the Ti / P compound is TiP2O7 or Ti3(PO4)4, and the Li compound is C2H3O2Li or LiOH.
2. The method according to claim 1, characterized in that In step (1), the mass ratio of BLiO2, Li2O and B4Li2O7 is 0.6-1:0.6-1:0.5-1; Preferably, the rotation speed of the mixing ball mill in step (1) is 100 to 1500 rpm; the mixing ball milling time is 0.5 to 8.0 hours; and the ball-to-material ratio of the mixing ball mill is 2 to 20:
1.
3. The method according to claim 1, characterized in that In step (1), the pre-sintering temperature is 100-800° C.; the pre-sintering constant temperature time is 1-6.0 hours; and the pre-sintering atmosphere is one of argon and nitrogen.
4. The method according to claim 1, characterized in that In step (2), the zirconium source is one or more selected from Zr(CO3)2, Zr(OH)4, ZrO2, Zr0.92O2Y0.08, Zr0.97O2Y0.03, Zr(CH3COO)4, ZrB2, ZrF4, ZrSiO4, Li2ZrO3, Zr(HPO4)2, ZrCl4, Zr(CH3COO)4·4H2O, Zr(C6H5O7)2, Zr(NO3)4, and ZrS2; The lithium source is one or more selected from LiOH, LiOH·H2O, Li2CO3, LiNO3, Li3BO3, LiBO2, Li2O, LiI, LiCl or C2H3O2Li; Preferably, the mass of the dopant in step (2) accounts for 0.01% to 6% of the total mass of the lithium source, lithium borate and zirconium source, wherein the mass ratio of the lithium source, lithium borate and zirconium source is 1 to 10: 1 to 3: 1 to 3; Preferably, in step (2), the mass ratio of the total mass of the lithium source, lithium borate and zirconium source to TiO2 is 1.0:0.0001-0.02; The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to AlPO4 is 1.0:0.0001-0.02; The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to Al(OH)3 is 1.0:0.0001-0.02; The mass ratio of the total mass of the lithium source, lithium borate and zirconium source to Al2O3 is 1.0:0.0001-0.
06.
5. The method according to claim 1, characterized in that In step (2), the rotation speed of the dry and wet mixed ball milling is 200 to 2500 rpm; the time of the dry and wet mixed ball milling is 1.0 to 10.0 h; and the ball-to-material ratio of the dry and wet mixed ball milling is 3 to 20:
1.
6. The method according to claim 1, characterized in that In step (3), the tableting pressure is 18 to 36 MPa; the tableting time is 1 to 20 s; Preferably, in step (3), the primary sintering temperature is 200-2400° C.; the primary sintering time is 2-32 hours; the primary sintering pressure is slightly positive or slightly negative, the slightly positive pressure is 10-200 Pa, and the slightly negative pressure is -15--180 Pa.
7. The method according to claim 1, characterized in that In step (4), the mass ratio of the doped modified lithium zirconium borate to the total amount of the coating agent is 1:0.0001-0.040; Preferably, the mass ratio of doped modified lithium zirconium borate to C2H3O2Li is 1:0.0001-0.020; The mass ratio of doped modified lithium zirconium borate to LiOH is 1:0.0001-0.020; The mass ratio of doped modified lithium zirconium borate to TiP2O7 is 1:0.0001-0.020; The mass ratio of doped modified lithium zirconium borate to Ti3(PO4)4 is 1:0.0001-0.010; The mass ratio of doped modified lithium zirconium borate to Al(OH)3 is 1:0.0001-0.
010.
8. The method according to claim 1, characterized in that In step (4), the tableting pressure is 10 to 20 MPa; the tableting time is 1 to 10 s; Preferably, in step (4), the secondary sintering temperature is 100-1100° C.; the secondary sintering time is 1-10 h; the secondary sintering pressure is slightly positive or slightly negative, the slightly positive pressure is 10-150 Pa, and the slightly negative pressure is -15--150 Pa.
9. An oxide solid electrolyte material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the oxide solid electrolyte material according to claim 9 in the preparation of a secondary battery.
Citation Information
Patent Citations
Solid electrolyte, preparation method thereof, protected positive electrode comprising same, electrochemical cell and electrochemical device
CN113764724A
Lithium oxide composite solid electrolyte, preparation method and application
CN117996166A
Positive electrode active material for solid-state lithium secondary battery and method for producing positive electrode active material for solid-state lithium secondary battery
CN118661293A
Lithium-mixed coated modified ternary positive electrode material as well as preparation method and application thereof
CN119133403A
High-nickel ternary positive electrode material using lithium fast-ion conductor as coating layer, preparation method therefor, and application thereof
WO2024113626A1
Cited By
Solid-state electrolyte precursor, preparation method of solid-state electrolyte, solid-state electrolyte and solid-state battery
CN120413836A
Preparation method of high-ionic-conductivity lithium-gallium-zirconium-oxygen-based oxide solid electrolyte
CN122224938A